Health Financing in Zambia - Masiye, Felix (World Bank, Washington, DC, 2019)
The 2012 national health policy is the overarching health policy framework in Zambia. The policy takes a human rights approach to health care provision, where all citizens are entitled to basic health care (Ministry of Health 2012). The policy is actualized through successive five-year national health strategic plans. Operationally, Zambia’s health system is centralized, with delegated responsibilities from the center to lower levels of the health care delivery system. The Ministry of Health plays a dual role of policy formulation and strategic planning and delivery of health services, with provincial and district health offices being upwardly accountable to the Ministry of Health headquarters. Going forward, Zambia is in the process of launching two major reforms which will further affect the organization of the health sector. These are (a) implementation of the National Decentralization Policy, and (b) introduction of a National Health Insurance (NHI) scheme. The PHC function (including transfer of PHC staff to local government authorities) is among the front runner for decentralization. If national decentralization is fully implemented, it will affect the way health services are organized, delivered, and financed in the country. Thus, adequate preparations in the health sector are required to minimize challenges. Secondly, Zambia enacted the NHI Act in April 2018 which provides the legal mandate to establish the NHI management authority, and the NHI scheme. At the time of this study, it was envisaged that implementation of the NHI scheme will be done in a phased manner with a view of covering the entire population in the medium to long term. However, depending on the final design and implementation process, the NHI will have a substantial effect on the financing and delivery of health programs and services in Zambia. One of the immediate challenges will be providing insurance cover to the informal sector and indigent people in rural areas.